Motherhood Behind Bars: Effects of Incarceration on Parenting and Child Custody in the selected Correctional Facilities, the United States of America (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This qualitative study investigates how incarceration impacts motherhood, examining the emotional, legal, and identity-related challenges faced by incarcerated mothers. Drawing on feminist criminology and strain theory, it explores how gendered social structures, and personal stressors intersect to affect women’s maternal roles while imprisoned. Based on interviews with incarcerated mothers across U.S. correctional facilities, the study highlights the disruption of parent–child bonds, fears of losing custody, and the enduring stigma of being labeled “bad mothers.” Despite these challenges, many women demonstrate resilience, maintaining their maternal identities and striving for reunification through adaptive coping strategies. The findings underscore the urgent need for policy reforms, including family-centered prison programs, safeguards against automatic termination of parental rights, and robust reentry support. By centering the lived experiences of incarcerated mothers, the research contributes to feminist criminology and demonstrates how mitigating incarceration-related strain is crucial for promoting rehabilitation, preserving family unity, and disrupting intergenerational incarceration cycles.